2001
DOI: 10.1088/0957-0233/12/8/342
|View full text |Cite
|
Sign up to set email alerts
|

Applications and evaluation of two-line atomic LIF thermometry in sooting combustion environments

Abstract: Temperature measurements using planar laser-induced fluorescence (PLIF) are most often associated with experimental challenges. In addition, no PLIF technique is generally applicable in all kinds of environment. Especially under sooting conditions problems are prone to arise, which limits the use of these techniques. In this paper the two-line atomic fluorescence (TLAF) technique was investigated in sooting environments. Indium atoms were used as thermometry species and seeded into the combustion region. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…LIF thermometry has most commonly been employed to probe in situ flame radical OH or seeded NO [7][8][9]. However, the narrow range of temperature and mixture fraction over which OH exists in a flame limits its general application for thermometry [10]. Likewise, NO-LIF has limitations because it can suffer from background interferences in the presence of soot [9].…”
Section: Introductionmentioning
confidence: 99%
“…LIF thermometry has most commonly been employed to probe in situ flame radical OH or seeded NO [7][8][9]. However, the narrow range of temperature and mixture fraction over which OH exists in a flame limits its general application for thermometry [10]. Likewise, NO-LIF has limitations because it can suffer from background interferences in the presence of soot [9].…”
Section: Introductionmentioning
confidence: 99%
“…Of the naturally occurring species within a flame, the OH radical is one of the most commonly used [8,[14][15][16]. In nonpremixed flames, OH only exists over a small range of temperature and mixture fraction, and so is not well suited for general measurements [17]. Furthermore, in fuel-rich flames, the OH concentration is low so that it is poorly suited to simultaneous measurements with soot, which is typically found in the fuel-rich side of the reaction zone [18].…”
Section: Introductionmentioning
confidence: 99%
“…Indium has good sensitivity over the temperature range ∼800-2800 K [29] and both wavelengths are in the visible (namely, 410 and 450 nm), where interferences are less pronounced than in the UV range, where many spectral species need to be excited. Recent feasibility studies [17,27] have shown that TLAF with indium holds promise for temperature measurement in a highly sooting environment. The indium is introduced to the system as indium chloride, which is dissolved in water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inherently, indium signal can only be obtained from the post combustion region of the flame. 4 The use of liquid seeding systems in flame measurements introduces various complications to the combustion system. Aspirating seeders generate a range of droplet sizes, only some of which successfully join the carrier gas stream; excess must be drained off to diminish problems of clogging and condensation on instrument surfaces.…”
Section: Introductionmentioning
confidence: 99%